Short-term exposure to chrysin promotes proliferative responses in the ventral male prostate and female prostate of adult gerbils - Campos, Mônica S. [UNESP]; Silva, João P. A.; Lima, Danilo S.; Regasini, Luis O. [UNESP]; Marques, Mara Rúbia; Biancardi, Manoel F.; Taboga, Sebastião R. [UNESP]; Santos, Fernanda C. A. (Wiley, 2019)
Chrysin (5,7-dihydroxyflavone) is a bioactive compound found in different fruits, vegetables, honey and propolis. This flavone has been suggested for the treatment of reproductive dysfunction, mainly because of its antioxidant and hormonal properties. However, the effects of this polyphenol on the prostate are still poorly understood. The purpose of this study was to evaluate the effects of short-term chrysin exposure on the ventral male and female prostates of adult gerbils. To evaluate the androgenic potential of chrysin, gerbils were also exposed to testosterone. Male and female gerbils were exposed to chrysin (50 mg/kg/day, orally) or testosterone cypionate (1 mg/kg/week, subcutaneously) for 3, 7 and 21 days. Prostates were dissected for morphological, stereological and immunohistochemical analyses. Serum levels of testosterone and 17β-estradiol were measured by ELISA. Serum testosterone levels were not increased by chrysin supplementation in males or females. However, only females treated with chrysin for 21 days showed an increase in estradiol levels. Increased androgen receptor immunoreactivity, higher proliferation rates and glandular hyperplasia were observed in male and female prostates for all chrysin treatment times. Additionally, increased oestrogen receptor alpha immunoreactivity was observed in all chrysin-treated females. Although chrysin and testosterone promoted similar morphological changes in the gerbil prostate, chrysin supplementation was less deleterious to prostate health, since it resulted in lower incidence of hyperplasia and an absence of neoplastic foci.
Keywords: androgen receptor; flavonoids; histopathology; immunohistochemistry; oestrogen receptor